Compassion for individual and collective futures: An ethnographic study of prioritization dilemmas in the Danish welfare state - Anna Brueckner Johansen; Mette N. Svendsen (Journal of Critical Public Health, 2026)
In 2019, the Danish health authorities rejected a medicine targeting a small group of patients with a rare eye disease due to ‘unreasonably high pricing’. Following sustained public pressure and continuing negotiations, the medicine was eventually approved as standard treatment. But the prioritization dilemma and public debate brought into sharp relief how seemingly contradictory collective and individual futures intersect in the Danish welfare state, and how affect shapes the articulations of these futures. In public health scholarship, the role of affect in prioritization dilemmas remains underexplored. This paper takes up this gap. Drawing on ethnographic fieldwork among patients, relatives, the pharmaceutical industry and state-bureaucrats, we show that decision-making is shaped by compassion directed both towards the individual and the collectivity. Compassion is not only mobilized through narratives of individual suffering and exceptionalism. Rather, prioritization stakeholders also frame the welfare state as an object of care, evoking compassion for the moral and economic sustainability of a future welfare state collectivity.